2011
DOI: 10.1007/s10439-011-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Spanning Tree Reflects the Alterations of the Default Mode Network During Alzheimer’s Disease

Abstract: This study analyzes the connectivity pattern of the default mode network (DMN) in patients with Alzheimer's disease (AD) in comparison with young and elderly controls using the minimum spanning tree (MST). This tree is a tool from graph theory and connects all the nodes of a graph with the minimum cost. The findings revealed that the alterations of the basic structure represented by the MST might provide valuable insights about the physiopathology of the disease. Additionally, by making use of the MST for func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…And the hierarchical clustering in combination with the MST has been used in different cognitive domains. Hierarchical clustering analysis of the MST showed that the connections between the parahippocampal gyrus and posterior cingulate gyrus were disrupted in Alzheimer patients [42]. Impaired communication between functional clusters in AD was found in one MEG study [46].…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…And the hierarchical clustering in combination with the MST has been used in different cognitive domains. Hierarchical clustering analysis of the MST showed that the connections between the parahippocampal gyrus and posterior cingulate gyrus were disrupted in Alzheimer patients [42]. Impaired communication between functional clusters in AD was found in one MEG study [46].…”
Section: Complexitymentioning
confidence: 99%
“…In a study of Multiple Sclerosis, findings indicate that MST network analyses were able to detect network changes in the Multiple Sclerosis (MS) patients [41]. In the study of Alzheimer's disease, MST was regarded as an effective method for analyzing cortical networks [42].…”
Section: Complexitymentioning
confidence: 99%
“…The first fMRI study that analysed the MST itself was performed on a data set set (#2-2000-1118W) from an international repository of raw fMRI data (www.fmridc.org) (Ciftçi, 2011). This data set consists of fMRI recordings in 14 healthy young subjects, 14 healthy elderly controls and 13 patients with "clinical dementia" during a simple sensory motor task.…”
Section: Pioneering Workmentioning
confidence: 99%
“…Hierarchical clustering analysis of the MST showed that the connection between the hippocampus/parahippocampal gyrus on the one hand to the precuneus and posterior cingulate gyrus on the other hand, that is normally mediated by the angular gyrus and the inferior temporal gyrus, was disrupted in Alzheimer patients. Ciftçi (2011) concluded that the MST carries information about the clustering of the network.…”
Section: Pioneering Workmentioning
confidence: 99%
See 1 more Smart Citation